Primary prevention of fat and weight gain among obesity susceptible healthy weight preschool children. Main results from the "Healthy Start" randomized controlled intervention. Issue 4 (6th October 2020) - Olsen, Nanna Julie; Ängquist, Lars; Frederiksen, Peder; Lykke Mortensen, Erik; Lilienthal Heitmann, Berit
Summary: Background: A vital public health challenge lies in understanding the primary drivers behind excessive weight gain among healthy weight individuals. Objectives: To examine if excessive weight and fat gain can be prevented among healthy weight, obesity susceptible children aged 2 to 6 years. Methods: Eligible children were identified based on information on either a high birth weight, maternal pre‐pregnancy obesity or maternal low educational level from national registries, and randomized into an intervention group, a control group and a shadow control group. All children with overweight at baseline were excluded from subsequent analysis (n = 196), while healthy weight children were included (n = 926). The intervention was designed to deliver improvements in diet and physical activity habits, optimization of sleep quantity and quality, and reduction of family stress. The average intervention period was 1.3 years. Results: Intention‐to‐treat analyses indicated a lower gain in percentage fat mass and a higher gain in fat‐free mass in the intervention group compared with the control group. However, the results should be interpreted with caution, as they were clinically small and borderline significant, only. Conclusion: This primary prevention intervention among young healthy weight children with susceptibility to future obesity had clinically small effects on growth and body composition. More interventions, conducting primary obesity prevention, are urgently needed.